Benefits of adaptive radiation therapy in lung cancer as a function of replanning frequency. Issue 4 (22nd March 2016) - Dial, Christian; Weiss, Elisabeth; Siebers, Jeffrey V.; Hugo, Geoffrey D.
Abstract : Purpose: To quantify the potential benefit associated with daily replanning in lung cancer in terms of normal tissue dose sparing and to characterize the tradeoff between adaptive benefit and replanning frequency. Methods: A set of synthetic images and contours, derived from weekly active breathing control images of 12 patients who underwent radiation therapy treatment for nonsmall cell lung cancer, is generated for each fraction of treatment using principal component analysis in a way that preserves temporal anatomical trends (e.g., tumor regression). Daily synthetic images and contours are used to simulate four different treatment scenarios: (1) a "no‐adapt" scenario that simulates delivery of an initial plan throughout treatment, (2) a "midadapt" scenario that implements a single replan for fraction 18, (3) a "weekly adapt" scenario that simulates weekly adaptations, and (4) a "full‐adapt" scenario that simulates daily replanning. An initial intensity modulated radiation therapy plan is created for each patient and replanning is carried out in an automated fashion by reoptimizing beam apertures and weights. Dose is calculated on each image and accumulated to the first in the series using deformable mappings utilized in synthetic image creation for comparison between simulated treatments. Results: Target coverage was maintained and cord tolerance was not exceeded for any of the adaptive simulations. Average reductions in mean lung dose (MLD) and volume of lung receiving 20 Gy or more ( V 20lung ) were 65 ± 49 cGy ( p = 0.000 01) and 1.1% ± 1.2% ( p = 0.0006), respectively, for all patients. The largest reduction in MLD for a single patient was 162 cGy, which allowed an isotoxic escalation of the target dose of 1668 cGy. Average reductions in cord max dose, mean esophageal dose (MED), dose received by 66% of the heart ( D 66heart ), and dose received by 33% of the heart ( D 33heart ), were 158 ± 280, 117 ± 121, 37 ± 77, and 99 ± 120 cGy, respectively. Average incremental reductions in MLD for the midadapt, weekly adapt, and full‐adapt treatments were 38, 18, and 8 cGy, respectively. Incremental reductions in MED for the same treatments were 57, 37, and 23 cGy. Reductions in MLD and MED for the full‐adapt treatment were correlated with the absolute decrease in the planning target volume ( r = 0.34 and r = 0.26). Conclusions: Adaptive radiation therapy for lung cancer yields clinically relevant reductions in normal tissue doses for frequencies of adaptation ranging from a single replan up to daily replanning. Increased frequencies of adaptation result in additional benefit while magnitude of benefit decreases.